Isolation and Characterization of Human Monoclonal Antibodies to Pneumococcal Capsular Polysaccharide 3 - Rachelle Babb; Christopher R. Doyle; Liise-anne Pirofski (Microbiology Spectrum, 2021)
ABSTRACT The current pneumococcal capsular polysaccharide (PPS) conjugate vaccine (PCV13) is less effective against Streptococcus pneumoniae serotype 3 (ST3), which remains a major cause of pneumococcal disease and mortality. Therefore, dissecting structure-function relationships of human ST3 pneumococcal capsular polysaccharide (PPS3) antibodies may reveal characteristics of protective antibodies. Using flow cytometry, we isolated PPS3-binding memory B cells from pneumococcal vaccine recipients and generated seven PPS3-specific human monoclonal antibodies (humAbs). Five humAbs displayed ST3 opsonophagocytic activity, four induced ST3 agglutination in vitro, and four mediated both activities. Two humAbs, namely, C10 and C27, that used the same variable heavy (VH) and light (VL) chain domains (VH3-9*01/VL2-14*03) both altered ST3 gene expression in vitro; however, C10 had fewer VL somatic mutations, higher PPS3 affinity, and promoted in vitro ST3 opsonophagocytic and agglutinating activity, whereas C27 did not. In C57BL/6 mice, both humAbs reduced nasopharyngeal colonization with ST3 A66 and a clinical strain, B2, and prolonged survival following lethal A66 intraperitoneal infection, but only C10 protected against lethal intranasal infection with the clinical strain. After performing VL swaps, C10VH/C27VL exhibited reduced ST3 binding and agglutination, but C27VH/C10VL binding was unchanged. However, both humAbs lost the ability to reduce colonization in vivo when their light chains were replaced. Our findings associate the ability of PPS3-specific humAbs to reduce colonization with ST3 agglutination and opsonophagocytic activity, and reveal an unexpected role for the VL in their functional activity in vitro and in vivo. These findings also provide insights that may inform antibody-based therapy and identification of surrogates of vaccine efficacy against ST3. IMPORTANCE Despite the global success of vaccination with pneumococcal conjugate vaccines, serotype 3 (ST3) pneumococcus remains a leading cause of morbidity and mortality. In comparison to other vaccine-included serotypes, the ST3 pneumococcal capsular polysaccharide (PPS3) induces a weaker opsonophagocytic response, which is considered a correlate of vaccine efficacy. Previous studies of mouse PPS3 monoclonal antibodies identified ST3 agglutination as a correlate of reduced ST3 nasopharyngeal colonization in mice; however, neither the agglutinating ability of human vaccine-elicited PPS3 antibodies nor their ability to prevent experimental murine nasopharyngeal colonization has been studied. We generated and analyzed the functional and in vivo efficacy of human vaccine-elicited PPS3 monoclonal antibodies and found that ST3 agglutination associated with antibody affinity, protection in vivo, and limited somatic mutations in the light chain variable region. These findings provide new insights that may inform the development of antibody-based therapies and next-generation vaccines for ST3.